Camera‐based independent couch height verification in radiation oncology. (8th September 2015) - Kusters, Martijn; Louwe, Rob; Kastel, Liesbeth Biemans‐van; Nieuwenkamp, Henk; Zahradnik, Rien; Claessen, Roy; van Seters, Ronald; Huizenga, Henk
Abstract : For specific radiation therapy (RT) treatments, it is advantageous to use the isocenter‐to‐couch distance (ICD) for initial patient setup. (1) Since sagging of the treatment couch is not properly taken into account by the electronic readout of the treatment machine, this readout cannot be used for initial patient positioning using the isocenter‐to‐couch distance (ICD). Therefore, initial patient positioning to the prescribed ICD has been carried out using a ruler prior to each treatment fraction in our institution. However, the ruler method is laborious and logging of data is not possible. The objective of this study is to replace the ruler‐based setup of the couch height with an independent, user‐friendly, optical camera‐based method whereby the radiation technologists have to move only the couch to the correct couch height, which is visible on a display. A camera‐based independent couch height measurement system (ICHS) was developed in cooperation with Panasonic Electric Works Western Europe. Clinical data showed that the ICHS is at least as accurate as the application of a ruler to verify the ICD. The camera‐based independent couch height measurement system has been successfully implemented in seven treatment rooms, since 10 September 2012. The benefits of this system are a more streamlined workflow, reduction of human errors during initial patient setup, and logging of the actual couch height at the isocenter. Daily QA shows that the systems are stable and operate within the set 1 mm tolerance. Regular QA of the system is necessary to guarantee that the system works correctly. PACS number: 87.55 QR